Urinary proteomics in diagnosis of kidney diseases (Journal of Chittagong Medical College Teachers' Association, 2011)
Keywords: proteomics; mass spectrometry; biomarkersDOI: http://dx.doi.org/10.3329/jcmcta.v22i1.9114 JCMCTA 2011; 22(1): 47-53